Reproductive Dysfunction in Women with PCOS: A Review Article - Abdulrahman R. Mahmood; Mohamad R. Abdullah; Husam S. Khalaf; Waled Abdo Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Polycystic ovary syndrome (PCOS) is a significant cause of infertility due to ovulation dysfunction in women of childbearing age. Although the pathogenesis of PCOS is still not clear, many studies have shown that many factors within the ovary promote infection. With this syndrome, the disruption of the natural monthly ovulation process causes an imbalance in the body’s hormones, and the high level of insulin in the body and the blood sugar imbalance leads to the occurrence of hyperandrogenism, which is the main factor for the occurrence of pathogens, in addition to genetic factors, if any. This study aims to identify this disease and its most important causes, symptoms, and modern treatments to prevent and get rid of it. Polycystic ovarian syndrome is diagnosed based on the presence of anovulation associated with biochemical or clinical hyperandrogenism, and the new diagnostic criteria at the Rotterdam Conference 2003 are the basis for the diagnosis now. Obesity, infertility, irregular menstruation, recurrent miscarriage, and hirsutism are essential factors that must be treated to have a healthy pregnancy.